Sudden Death with Dual Organ Pathologies–An Autopsy -based Case Report - Mukul Sharma; Kimi Soumya Padhi; Govinda Balmuchu; Prachi Nemani; ManasRanjan Sahu (Institute of Medico-legal Publications Pvt Ltd, 2022)
Sudden death due to cardiac cause is considered as a major health problem worldwide accounting for 15–20% of all deaths and cardiomyopathies account for 10–15% of the cases.According to the 2016 WHO classification, angiomatous meningioma is a rare subtype of meningioma classified as Grade I. It is an aggressive variety with a fair prognosis, with typical symptoms including headache and seizures.We present a case of a 60-year-old man brought to the morgue for autopsy with a history of progressive left-sided weakness and headache for several months with no prior diagnosis or treatment for the same because of current pandemic of COVID-19.On conducting medicolegal autopsy significant pathologies in heart and brain were found which could have contributed to the cause of death